Digitalisasi UMKM Berbasis Komoditas Lokal Kopi dan Kayu Manis Jorong Koto Panjang - Rido Putra; Hanayatul Findira; Raudatul Fitri; Viona Razakinta; Wahyu Andika; Wulan Dynanti (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a pillar of the national economy, including in rural areas such as Nagari Dalko, Jorong Koto Panjang, Agam Regency. Kalidin coffee and cinnamon are two local commodities with high sales value but have not been optimally managed, especially in terms of marketing and distribution. This article discusses the digitalization strategy of MSMEs as a solution to increase the economic value of local commodities through the use of digital technology. The research method used is descriptive qualitative with a community-based participatory approach. The analysis shows that digitalization can increase market access, improve production processes, and develop product branding. The digitalization of MSMEs is expected to not only increase the competitiveness of local products but also create an inclusive and sustainable digital entrepreneurship ecosystem.